Cycling performance following adaptation to two protocols of acutely intermittent hypoxia - Bonetti, D. L.; Hopkins, W. G.; Lowe, T. E.; Kilding, A. (International Journal of Sports Physiology and Performance, 2009)
Purpose: Adaptation to acutely intermittent hypoxic exposure appears to produce worthwhile enhancements in endurance performance, but the current 5-min duration of hypoxia and recovery intervals may not be optimal. Methods: Eighteen male competitive cyclists and triathletes were randomized to one of two intermittent-hypoxia groups, and nine similar athletes represented a control group. Athletes in the hypoxia groups were exposed to 60 min per day of intermittent hypoxia consisting of alternating intervals of hypoxia and normoxia lasting either 3 or 5 min. Exposures were performed at rest for 5 consecutive days per week for 3 wk. Oxygen saturation, monitored with pulse oximetry, was reduced progressively from 90% (day 1) to 76% (day 15). All athletes maintained their usual competitive-season training throughout the study. Incremental and repeated-sprint tests were performed pre, 3 d post, and 14 d postintervention. Venous blood at rest was sampled pre, mid-, and postintervention. Results: There were no clear differences between effects of the two hypoxic treatments on performance or various measures of oxygen transport, hematopoiesis, and inflammation. Compared with control, the combined hypoxic groups showed clear enhancements in peak power (4.7%; 90% confidence limits, ±3.1%), lactate-profile power (4.4%; ±3.0%), and heart-rate profile power (6.5%; ±5.3%) at 3 d postintervention, but at 14 d the effects were unclear. Changes in other measures at 3 and 14 d postintervention were either unclear or unremarkable. Conclusion: Acutely intermittent hypoxia produced substantial enhancement in endurance performance, but the relative benefit of 3- vs 5-min exposure intervals remains unclear.